Efficacy of antibiotic prophylaxis in patients with cancer and hematopoietic stem cell transplantation recipients: A systematic review of randomized trials. (5th July 2019) - Egan, Grace; Robinson, Paula D.; Martinez, Juan P. D.; Alexander, Sarah; Ammann, Roland A.; Dupuis, L. Lee; Fisher, Brian T.; Lehrnbecher, Thomas; Phillips, Bob; Cabral, Sandra; Tomlinson, George; Sung, Lillian
Abstract: Purpose: To determine the efficacy and safety of different prophylactic systemic antibiotics in adult and pediatric patients receiving chemotherapy or undergoing hematopoietic stem cell transplantation (HSCT). Methods: We conducted a systematic review and performed searches of Ovid MEDLINE, MEDLINE in‐process and Embase; and Cochrane Central Register of Controlled Trials. Studies were included if patients had cancer or were HSCT recipients with anticipated neutropenia, and the intervention was systemic antibacterial prophylaxis. Strategies synthesized included fluoroquinolone vs no antibiotic/nonabsorbable antibiotic; fluoroquinolone vs trimethoprim‐sulfamethoxazole; trimethoprim‐sulfamethoxazole vs no antibiotic; and cephalosporin vs. no antibiotic. Fluoroquinolone vs cephalosporin and levofloxacin vs ciprofloxacin were compared by network meta‐analysis. Primary outcome was bacteremia. Results: Of 20 984 citations screened, 113 studies comparing prophylactic antibiotic to control were included. The following were effective in reducing bacteremia: fluoroquinolone vs no antibiotic/nonabsorbable antibiotic (risk ratio (RR) 0.56, 95% confidence interval (CI) 0.41‐0.76), trimethoprim‐sulfamethoxazole vs no antibiotic (RR 0.59, 95% CI 0.41‐0.85) and cephalosporin vs no antibiotic (RR 0.30, 95% CI 0.16‐0.58). Fluoroquinolone was not significantly associated with increased Clostridium difficile infection (RR 0.62, 95% CI 0.31‐1.24) or invasive fungal disease (RR 1.28, 95% CI 0.79‐2.08) but did increase resistance to fluoroquinolone among bacteremia isolates (RR 3.35, 95% CI 1.12 to 10.03). Heterogeneity in fluoroquinolone effect on bacteremia was not explained by evaluated study, population, or methodological factors. Network meta‐analysis revealed no direct comparisons for pre‐specified analyses; superior regimens were not identified. Conclusions: Fluoroquinolone, trimethoprim‐sulfamethoxazole, and cephalosporin prophylaxis reduced bacteremia. A clinical practice guideline to facilitate prophylactic antibiotic decision‐making is required. Abstract : A systematic review was conducted to determine the efficacy and safety of antibiotic prophylaxis in patients with cancer and hematopoietic stem cell transplantation recipients. Heterogeneity in the effect of fluoroquinolone prophylaxis was evaluated and a network meta‐analysis was performed to contrast therapies in which no direct comparative trials exist. The systematic review results indicate fluoroquinolone, trimethoprim‐sulfamethoxazole, and cephalosporin prophylaxis reduce bacteremia but do not reduce overall mortality.